Biomimetic Approaches for Separated Regeneration of Sensory and Motor Fibers in Amputee People: Necessary Conditions for Functional Integration of Sensory–Motor Prostheses With the Peripheral Nerves - Guedan-Duran, Atocha; Jemni-Damer, Nahla; Orueta-Zenarruzabeitia, Irune; Guinea, Gustavo Víctor; Perez-Rigueiro, José; Gonzalez-Nieto, Daniel; Panetsos, Fivos (Frontiers in Bioengineering and Biotechnology, 2020)
The regenerative capacity of the peripheral nervous system (PNS) after an injury is limited, and a complete function is not recovered, mainly due to the loss of nerve tissue after the injury that causes a separation between the nerve ends and to the disorganized and intermingled growth of sensory and motor nerve fibers that cause erroneous reinnervations. Even though the development of biomaterials is a very promising field, today no significant results have been achieved. In this work we study not only the characteristics that should have the support that will allow the growth of nerve fibers, but the molecular profile necessary for a specific guidance. To do this, we carried out an exhaustive study of the molecular profile present during the regeneration of the sensory and motor fibers separately, as well as of the effect obtained by the administration and inhibition of different factors involved in the regeneration. In addition, we offer a complete design of the ideal characteristics of a biomaterial, that allows the growth of the sensory and motor neurons in a differentiated way, indicating: (1) size and characteristics of the material (2) necessity to act at the micro level, on small groups of neurons (3) combination of molecules and specific substrates and (4) temporal profile of those molecules expression throughout the regeneration process. The importance of the design we offer is that: it respects the complexity and characteristics of the regeneration process; it indicates the appropriate temporal conditions of molecular expression, in order to obtain a synergistic effect; it takes into account the importance of considering the process at the group of neurons level; it gives an answer to the main limitations in current studies.